Novel and Romance - McDermott, Hubert. author. aut Link
XI, 257 p.
Keywords: McDermott argues that the novels of the 18th century should be seen as part of an age-old European tradition going back to Homer rather than as a unique English event. He examines European fictional narratives and romance and their influence on authors such as Richardson and Fielding.